ZnFe-LDH/GO nanocomposite coated on the glass support as a highly efficient catalyst for visible light photodegradation of an emerging pollutant - Motlagh, Parisa Yekan; Khataee, Alireza; Hassani, Aydin; Rad, Tannaz Sadeghi (Elsevier, 2020)
This study reports the fabrication of ZnFe-layered double hydroxides with sulfate-intercalated anion (ZnFe-SO4-LDH) modified with graphene oxide (GO) by chemical co-precipitation method. They were then coated on the glass substrates (denoted as ZnFe-LDH/GO/GS). The XRD, SEM, EDX, X-ray Dot-mapping, FTIR, AFM, UV-Vis DRS, and PL analyses were used for the characterization of the as-synthesized sample. The photocatalytic implementation of the as-prepared photocatalyst was scrutinized for the degradation of phenazopyridine hydrochloride (PhP) from the solution under visible light irradiation. The prepared photocatalyst showed photocatalytic performance of elimination PhP, the degraded rate of pollutant could reach 60.01% in 150 min of photocatalysis process under the optimum conditions: initial PhP concentration of 15 mg/L, pH of 8 (natural pH), and 3 photocatalysts plates. The addition of 1 mmol/L of potassium persulfate (k(2)S(2)O(8)) caused the degradation efficiency of 93.95% within the 150 min of photocatalytic process. Trapping experiments indicated the influence order of O-2(-center dot) > center dot OH > h(+) for the ROSs present in decomposition. The transformation of five intermediates of PhP produced in the photocatalytic degradation process was identified by the GC-MS technique. 60% COD removal efficiency was achieved after 300 min of photocatalytic reaction confirming mineralization of the PhP solution. Finally, a reusability test of ZnFe-LDH/GO/GS photocatalyst in the PhP degradation revealed that almost 12% drop occurred after five successive cycles. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Advanced oxidation process; Layered double hydroxides; Visible light photocatalyst; Modified graphene oxide; Nanocatalyst; Phenazopyridine